Jazz Age Josephine - Winter, Jonah 1962- (Atheneum Books for Young Readers, 2012)
A tribute to the life of the iconic jazz entertainer depicts her disadvantaged youth in a segregated America, her unique performance talents, and the irrepressible sense of style that helped her overcome racial barriers